Analysis of the Impact of the Pencak Silat Coach Training Program on Athlete Development in North Sumatra in 2024 - Keliat, Pedomanta; Munawar, Ahmad Al (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to analyze the impact of the Pencak Silat coach training program on athlete development in North Sumatra in 2024. Using a quantitative approach and an experimental design, this research compares two groups of athletes: one trained by coaches who attended the training program and one trained by coaches who did not. Data were collected through questionnaires, skill tests, observations, and documentation of athletes' achievements. The results showed that athletes trained by coaches who attended the training program exhibited better technical skills, physical qualities, mental strength, and motivation compared to those trained by non-participating coaches. Additionally, athletes trained by coaches who participated in the program performed better in provincial and national competitions. Based on statistical analysis, the coach training program positively influenced athlete development with a p-value < 0.05. This study concludes that the Pencak Silat coach training program can enhance coaching quality and athlete performance, making it essential to continue and expand its implementation throughout North Sumatra.